Merevolusi Keuangan Islam: Memanfaatkan Kekuatan Bank Wakaf untuk Transformasi Sosial Ekonomi - Ickhsanto Wahyudi (Al-Awqaf: Jurnal Wakaf dan Ekonomi Islam, 2024)
This study provides a comprehensive review of waqf banks, an innovative financial institution in Islamic finance. Through a systematic analysis of 16 Scopus-indexed articles, we explore the evolution, potential, and challenges of waqf banks in addressing socio-economic issues in Muslim-majority countries, with a focus on Indonesia. Our findings reveal that waqf banks, which uniquely combine charitable endowments with microfinance principles, offer a promising solution for poverty alleviation and economic development. These institutions demonstrate particular effectiveness in providing financial services to underserved communities, supporting micro, small, and medium enterprises (MSMEs), and potentially revolutionizing education financing. The review traces the research progression from theoretical frameworks to empirical impact assessments, highlighting the growing recognition of waqf banks' potential. We identify various operational models, each tailored to specific socio-economic needs, ranging from integrated Islamic banking approaches to specialized micro-waqf institutions. Despite their promise, waqf banks face significant challenges, including regulatory hurdles, limited public awareness, and the need for enhanced operational efficiency. Our analysis points to several promising directions for future research and development. These include the integration of financial technology to expand reach and efficiency, exploration of cross-border waqf bank networks, development of hybrid models combining waqf principles with other financial instruments, and the crucial need for standardized impact assessment frameworks. This review contributes to the growing body of literature on Islamic social finance, offering valuable insights for researchers, policymakers, and practitioners in developing effective waqf bank models to address persistent development challenges.